THE RELATIONSHIP BETWEEN EMOTIONAL INTELLIGENCE AND ORGANIZATIONAL COMMITMENT - Theng, Bestadrian P Theng; Susanto, Agus; Tanady, Darwan; Assaly, Arifin; Djakasaputra, Arifin (Journal of Industrial Engineering & Management Research, 2021)
Employees are one of the important elements in every organization. Without employees, it will be difficult for organization to achieve their goal in this tight business competition. Based on the initial data that obtain in this research, it is know that there is a employees turnover every year in CV. Makmur Jaya Medan. One of the factors is due to employees in this company have a low emotional intelligence and can't commit in one organization for long term. Therefore, the problem of this research is to find "Is there relationship between emotional intelligence and organizational commitment at CV. Makmur Jaya Medan?". Emotional Intelligence generally assumed as an individual capability to recognize its own emotion and others, but it can become influential tools in the Human Resource (H.R.) for managing employees. Emotional Intelligence can motivate employees to become aware with themselves, capable in taking responsibility of their own work and become more commit towards the organization. In this research, the writer use census sampling which takes all 39 employees as a respondent. The method of collecting data is based on primary data and secondary data. In analyzing questionnaires, the writer use validity test, reliability test, statistic test, correlation test, determination test, normality test, linear regression, and hypothesis test to analyze the questionnaires. The result of this research is that emotional Intelligence has a 64.9% relate towards organizational commitment based on determination test at CV. Makmur Jaya Medan. Z counted â‰¥ +Z table (4.975 â‰¥ 1.96), means the Null hypothesis (Ho) is rejected and the Alternative hypothesis (Ha) is accepted. In conclusion, the writer would like to give recommendation for the company's leader to become flexible leader, listen to the employees, giving a clear feedback and respect to his employees. With that, the employees will feel that they still have value in this company. Keywords: Emotional Intelligence, Organizational Commitment